Global representation of heart failure clinical trial leaders and collaborators: a systematic bibliometric review 2000–2020. (14th October 2021) - Zhu, J; Le, N; Wei, S; Zuhlke, L; Lopes, R; Zannad, F; Van Spall, H G C
Abstract: Aims: Heart Failure (HF) has a disproportionate burden in low- and middle-income countries. The geographic representation of those who lead HF randomized clinical trials (RCTs) may not reflect the geographic burden of disease. We assessed temporal trends and trial characteristics associated with leadership outside Europe and North America, and explored whether there was a geographic association between trial leadership and participant enrolment. Methods and results: We searched MEDLINE, EMBASE, and CINAHL for HF RCTs published in journals with an impact factor ≥10 between January 1, 2000, and June 17, 2020. We used the Jonckheere-Terpstra test to assess temporal trends and multivariable logistic regression models to determine associations between predictor and outcome variables. There were 414 eligible RCTs. Only 80 of 828 trial leaders (9.7%; 95% CI: 7.8% to 11.8%), and 453 of 4656 collaborators (9.7%; 95% CI: 8.8% to 10.6%) were from regions outside Europe and North America, with no temporal change in geographic representation. The odds of trial leadership outside Europe and North America were significantly lower with industry versus public funding (OR: 0.33; 95% CI: 0.15 to 0.75; P=0.008). Trial leadership outside Europe and North America was associated with enrolment of patients outside Europe and North America (OR: 10.0; 95% CI 5.6–19.0; P<0.001). Conclusion: Trial leadership outside Europe and North America is rare, particularly in industry funded trials, and is associated with participant enrolment in regions with disproportionate disease burden. Building research capacity and networks in under-represented regions could increase generalizability of trial results. FUNDunding Acknowledgement: Type of funding sources: None.